Comparative Study on Physiological Responses and Gene Expression of Bud Endodormancy Release Between Two Herbaceous Peony Cultivars (Paeonia lactiflora Pall.) With Contrasting Chilling Requirements - Wang, Xiaobin; Zhang, Runlong; Huang, Qiaoyu; Shi, Xiaohua; Li, Danqing; Shao, Lingmei; Xu, Tong; Horvath, David P.; Xia, Yiping; Zhang, Jiaping (Frontiers in Plant Science, 2022)
With the global temperature increase, diverse endogenous factors and environmental cues can lead to severe obstacles to bud endodormancy release for important economic plants, such as herbaceous peony (Paeonia lactiflora Pall.). Knowing the underlying mechanism in bud endodormancy release is vital for widely planting herbaceous peony at low latitudes with warm winter climates. A systematic study was carried out between the southern Chinese cultivar ‘Hang Baishao’ with low-chilling requirement (CR) trait and the northern cultivar ‘Zhuguang’ with high-CR trait. Peony buds were sampled at regular intervals under natural cold during the crucial bud endodormancy release stage. Physiology and morphology of the buds were observed, and the roles of reactive oxygen species (ROS) and relevant genes in the regulation of bud endodormancy release were also highlighted, which has been rather rare in previous bud dormancy studies of both herbaceous and tree peonies. The expression of the starch metabolism- and sucrose synthesis-related genes PlAMY PlSPS and PlSUS was lower in the high-CR ‘Zhuguang’ and corresponded to a lower content of soluble sugars. The expression of polyamine oxidase gene PlPAO2 correlated with a higher level of hydrogen peroxide (H2O2) in high-CR ‘Zhuguang’ than in low CR ‘Hang Baishao’ during bud endodormancy. Expression of PlMAPKKK5, an intermediate gene in the abscisic acid (ABA) response to ROS signaling, correlated with ROS levels and ABA content. We present the hypothesis that accumulation of ROS increases ABA content and decreases GA3 content and signal transduction leading to reduced expression of PlSVP and PlSOC1. Reduced cell division and increased cellular damage which probably blocked bud endodormancy release were also observed in high-CR ‘Zhuguang’ through histological observation and related genes expression. This study provides a comparative analysis on physiological responses and gene expression patterns of bud dormancy of geophytes in an increasingly unsuitable environment.